Changes in Fatigue Levels and Sleep Measures of Hospital Nurses During Two 12-Hour Work Shifts. (March 2021) - Cho, Hyeonmi; Brzozowski, Sarah; Arsenault Knudsen, Élise N.; Steege, Linsey M.
Abstract : OBJECTIVE: The aims of this study were to explore nurses' fatigue levels and sleep measures during two 12-hour consecutive day shifts and examine the relationships between nurses' fatigue levels within shifts and their previous-night sleep characteristics. BACKGROUND: Monitoring changes in fatigue and sleep is important to enable effective fatigue management. METHODS: This was a descriptive, repeated-measures study. Data were collected using surveys and actigraphy 4 times during each consecutive shift (7:00 am -7:30 pm ). RESULTS: General fatigue levels started trending up 4 hours after the start of work; highest levels were reported at 7:30 pm . Fatigue levels accumulated across consecutive shifts. Subjective sleep quality was higher the night before the 2nd shift than the night before the 1st shift. Nurses' poor sleep the night before a shift was related to increased fatigue levels during the next shift. CONCLUSION: It is important to consider when fatigue management interventions will be most effective and to consider previous-night's sleep when monitoring fatigue.